The Strategic Role of Hybrid Kiai Leadership in the Integration of Sufism, Technology, and the Transformation of Islamic Education - Sumarsi Sumarsi; Muhammad Rusdi Rasyid; Muhammad Syahrul Sambu; Moh. Harun Al Rosid; M. Kurma Nur Faifatur R (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
Study This leaves from the dynamics change social and developmental demanding digital technology transformation in the system of Islamic education, especially in the environment of Islamic boarding school, without removing the dimensions of spirituality that becomes the main foundation. Research objectives This is For analyze the role of strategic hybrid Kiai leadership in integrating values of Sufism, utilizing technology, and transforming Islamic education at the Islamic boarding school Cahaya Islam, Sorong City. Methods used are a qualitative approach with a case study design through technique data collection in the form of observation, in-depth interviews, and documentation, which is later analyzed in a way descriptive-interpretive way to understand patterns of leadership and practice education in Islamic boarding schools. Research results show that hybrid Kiai is capable of harmonizing values of Sufism like dhikr, tafakkur, and coaching morals with the use of digital technology in the learning process and management institutions in a way selective and based value. Technology is not positioned as a replacement for spirituality, but rather as an instrument amplifier in reach effectiveness of education. In addition, hybrid kiai leadership also functions as agent marked transformation​ with strengthening management data -driven, development curriculum integrative, as well as implementation system, further evaluation​ , measurable, and adaptive. Research conclusions. This confirms that the hybrid Kiai leadership model gives significant improvement in the quality of education in Islamic boarding schools, at the same time producing balanced students​ with spirituality, intellectuality, and the ability to adapt to the development of global technology.